2021
DOI: 10.15547/ast.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Date of ear emergence: a factor for notable changing the grain yield of modern winter wheat varieties in different environments of Bulgaria

Abstract: Abstract. Wheat is a crop with a very long growing season, during which it is subjected to prolonged exposure to many environmental factors. For this reason, the interaction of genotype with conditions is very common for any character of wheat. This study aims to determine whether the grain yield is affected by the change of the ear emergence date (EED) in various environments. In a four-year period, 30 current for national real grain production winter wheat varieties were studied. The EED and grain yield (GY)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, in a wide range of different environments, it is possible to combine a high index means with high stability (Figure 1). However, this stability is associated with a low mean of the indexes (Atanasova et al, 2009). Varieties with higher means averaged over the entire experiment (G1, G2, G4, G8, G14) showed high stability, while some of those with lower means (G15, G16, G17, G21) showed high variability.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, in a wide range of different environments, it is possible to combine a high index means with high stability (Figure 1). However, this stability is associated with a low mean of the indexes (Atanasova et al, 2009). Varieties with higher means averaged over the entire experiment (G1, G2, G4, G8, G14) showed high stability, while some of those with lower means (G15, G16, G17, G21) showed high variability.…”
Section: Resultsmentioning
confidence: 94%
“…This is an indication the combination of the two aspects of the grain -yield and quality is possible, but at compromise levels of each of them to have progressed in terms of quality as well (Bosi et al, 2022;Ilin et al, 2022). The question of what combination of yield and quality should be aimed at in practical breeding remains open, because with productivity above 9 t/ha, a "balance" between them is difficult to achieve (Dencic et al, 2007;Atanasova et al, 2009). In this study, an attempt was made to seek answers to the questions posed in direct dependence on specific environmental conditions and an up-to-date set of varieties with different genetics for both aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, differentiation in the time of emergence was observed in the investigated varieties, although they probably have identical genetic control factors according to the requirements for vernalization and photosensitivity. Similarly, Tsenov et al [42] reported on Bulgarian winter wheat varieties that also differed in grain-filling period. Liu et al [31] reported that the glaucosity of different organs is responsible for drought tolerance due to reduction in the leaf water potential, which is essential to ensure plants have a relatively high photosynthesis rate.…”
Section: Morphological Traits That Changed Over the Period From 2006 ...mentioning
confidence: 87%
“…This means that varieties with a stronger glaucosity of flag leaves and glaucosity of the neck of the culm will be later in maturity. A positive correlation between the time of ear emergence and grain yield was observed, although the change depended on environmental factors [42]. The glaucosity of the different tissues of wheat can have an important role in its resistance to biotic and abiotic stresses that will influence grain yield.…”
Section: The Most Related Morphological Traits Over the Yearsmentioning
confidence: 96%
“…На сьогодні у сучасному сільськогосподарському виробництві використовується багато ефективних засобів, що сприяють підвищенню врожайності пшениці, як однієї з найважливіших зернових культур [1]. Щороку реєструються нові сорти пшениці озимої з різноманітними сільськогосподарськими та функціональними характеристиками, які можна вирощувати в певному регіоні чи кількох регіонах нашої країни, удосконалюються технології вирощування [2,3]. Але, пошук ефективних, екологічно прийнятних агротехнологій, які гарантують стабільний високий урожай даної зернової культури при зниженні собівартості та негативного впливу засобів інтенсифікації на довкілля, залишається актуальним [4].…”
Section: вступunclassified